Quizizz As an Arabic Vocabulary Media Learning in Digitalization Era: Process, Weakness and Strengths - Rosita Ilhami; Wildana Wargadinata; Nur Hasan; Muhammad Ikhlas; Sayar Ahmad Najar (AL-TA'RIB : Jurnal Ilmiah Program Studi Pendidikan Bahasa Arab IAIN Palangka Raya, 2022)
Some students still have difficulty in learning Arabic. Various application platforms can be used by teachers as interesting learning media in the digital era. One of them is Quizizz, a game-based online learning media, it is very appropriate to use in the digital era to follow learning styles and increase students' enthusiasm for learning. So far, many have discussed Quizizz in learning, but no one has specifically discussed the process, weakness, and strengths of Quizizz. Therefore, this study focuses on exploring the perceptions of students who are not interested in the Arabic Language towards learning the Arabic Language using Quizizz media, which focuses on Arabic Vocabularies. The research method used in this research is case study with observation, interview, and documentation techniques. The results of the study found that the strengths of using Quizizz were to foster student enthusiasm in competing because there was a ranking system that appeared after answering the quiz, and was flexible in its use because there was no need to download applications that would fill the cellphone memory. As for the weakness, Quizizz requires a stable internet, which will make students rush and carelessly in answering quizzes because of the time limit.